2003
DOI: 10.1080/0892701031000061778
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Marine Natural Product-based Antifouling Paint

Abstract: Problems with tin and copper antifouling compounds have highlighted the need to develop new environmentally friendly antifouling coatings. Bacteria isolated from living surfaces in the marine environment are a promising source of natural antifouling compounds. Four isolates were used to produce extracts that were formulated into ten water-based paints. All but one of the paints showed activity against a test panel of fouling bacteria. Five of the paints were further tested for their ability to inhibit the sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(120 citation statements)
references
References 45 publications
1
110
0
9
Order By: Relevance
“…As early as 1999, it was reported that the active substances secreted by blue algae could inhibit the growth of diatoms [92]. Functional antifouling components have also been discovered in other organisms such as fungi [93], sponge [94] and some other bacteria [95,96].…”
Section: Biological Methodsmentioning
confidence: 99%
“…As early as 1999, it was reported that the active substances secreted by blue algae could inhibit the growth of diatoms [92]. Functional antifouling components have also been discovered in other organisms such as fungi [93], sponge [94] and some other bacteria [95,96].…”
Section: Biological Methodsmentioning
confidence: 99%
“…Upon collection, the soft-coral colonies were then put into plastic containers containing sterile seawaters and then were stored temporarily in a cool box. The samples were rinsed 39 with sterile seawaters to clean the bacteria that temporarily attached to the surface waters (Burgess et al 2003). The samples were homogenated and were serially diluted.…”
Section: Sampling and Isolation Of Bacterial Symbiontsmentioning
confidence: 99%
“…Senyawa ini juga mengandung nitrogen dalam bentuk amida atau indol yang memiliki aktivitas antibakteri dan antifungi (Takeshi et al, 2003, Atta-ur-Rahman & Choudhary, 2001). Burgess et al, (2003) dan Hellio et al, (2003) …”
Section: Alga Laut Sebagai Sumber Senyawa Bioaktifunclassified